The First Passage Time and Estimation of the Number of Level-Crossings for a Telegraph Process - Pogorui, A.A.; Rodríguez-Dagnino, R.M.; Kolomiets, T. (Український математичний журнал, 2015)
It is a well-known result that almost all sample paths of a Brownian motion or Wiener process {W(t)} have infinitely many zero-crossings in the interval (0, δ) for δ > 0. Under the Kac condition, the telegraph process weakly converges to the Wiener process. We estimate the number of intersections of a level or the number of level-crossings for the telegraph process. Passing to the limit under the Kac condition, we also obtain an estimate of the level-crossings for the Wiener process. Відомо, що майже всі ви6іркові траєкторії броунівського руху чи вінєрівського процесу {W(t) мають нескінченно багато нульових перетинів в інтервалі (0, δ) при δ > 0. За умови Каца телеграфний процес слабко збігається до вінерівського процесу. В роботі оцінюється число перетинів рівня для телеграфного процесу. Переходячи до границі за умови Каца, ми також отримуємо оцінку перетинів рівня для вінерівського процесу.